2003
DOI: 10.1097/01.asn.0000039578.55705.6e
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Mutations in the Gene for Autosomal Recessive Polycystic Kidney Disease (ARPKD/PKHD1)

Abstract: Abstract. Autosomal recessive polycystic kidney disease (ARPKD/PKHD1) is an important cause of renal-related and liver-related morbidity and mortality in childhood. Recently mutations in the PKHD1 gene on chromosome 6p21.1-p12 have been identified as the molecular cause of ARPKD. The longest continuous open reading frame (ORF) is encoded by a 67-exon transcript and predicted to yield a 4074 -amino acid protein ("polyductin") of thus far unknown function. By now, a total of 29 different PKHD1 mutations have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
224
4
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(254 citation statements)
references
References 31 publications
15
224
4
11
Order By: Relevance
“…Consistently, our previous analysis of mutations in a large cohort of ARPKD patients showed that patients with 2 truncating mutations displayed a severe phenotype with perinatal or neonatal demise. 18 However, in the absence of data concerning functional relevance of different PKHD1 protein motifs, it is impossible to precisely interpret the frequent missense mutations. In this respect, our study provides further evidence that the precise phenotype of hepatic and kidney disease in ARPKD patients correlates with the genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, our previous analysis of mutations in a large cohort of ARPKD patients showed that patients with 2 truncating mutations displayed a severe phenotype with perinatal or neonatal demise. 18 However, in the absence of data concerning functional relevance of different PKHD1 protein motifs, it is impossible to precisely interpret the frequent missense mutations. In this respect, our study provides further evidence that the precise phenotype of hepatic and kidney disease in ARPKD patients correlates with the genotype.…”
Section: Discussionmentioning
confidence: 99%
“…For reverse transcription, 1 g total RNA was primed with 1 g oligo d(T) [12][13][14][15][16][17][18] , and transcription was performed by Superscript II RT following the manufacturer's description (Invitrogen). PCR was run with 35 cycles (1 minute at 94°C, 45 seconds at 53°C to 55°C, and 1 to 2 minutes at 72°C).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were chosen for analysis if they showed typical clinical and/or histologic features of ARPKD as previously described in detail (2,5,8). We performed PKHD1 mutation analysis in a large cohort of .500 patients with polycystic kidney disease phenotypes using conventional Sanger sequencing or a targeted next-generation sequencing approach.…”
Section: Patientsmentioning
confidence: 99%
“…To date, .700 different PKHD1 mutations are known (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The longest open reading frame of PKHD1 comprises 66 exons and encodes a single-transmembrane protein, called polyductin/fibrocystin, which is mainly expressed in the kidney and liver/cholangiocytes (6,7,19).…”
Section: Introductionmentioning
confidence: 99%
“…[1] The causative factor is the mutations in the PKHD1 (chromosomal locus 6p12.2). [2] The disease has a wide clinical variation from stillbirth and neonatal demise to survival into adulthood; the carrier frequency for a PKHD1 mutation is estimated to be about 1:70 in general population. The majority of cases present in the neonatal period though the diagnosis may be suspected on prenatal ultrasound.…”
Section: Dear Sirmentioning
confidence: 99%